Case reportPseudoporphyria induced by hemodialysis - Bergler-Czop, Beata; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Pseudoporphyria is a condition identical to porphyria cutanea tarda (PCT) on clinical and histological grounds, but without any biochemical porphyrin abnormality. Excessive sunlight and UVA exposure (for example tanning beds), drugs such as: non-steroidal anti-inflammatory drugs, retinoids, antibiotics, diuretics and others are supposed to be etiological factors of pseudoporphyria. Cases of PCT and pseudoporphyria in patients with HCV infection and hemodialysed due to chronic renal failure were also described. Here, we describe a clinical case of a 57-year-old patient, who developed cutaneous changes on the face and the dorsal surfaces of hands clinically and histologically characteristic of PCT but with normal levels of urine porphyrins.